Influence of Digital Modality on Knowledge Transformation in BIM Design - Babangida Idi, Danfulani; Khaidzir, Khairul Anwar Mohamed; Sani Muhammad , Ali (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
There is no clear understanding as to whether complex design problem-solving activities such as conceptualization, sketching, actions, transformation, and reasoning can be readily circumscribed into Building Information Modeling (BIM) design. This research investigates the phenomenon of collaborative design based on the BIM framework using the protocol study technique. The protocol consists of eight (8) multidisciplinary design teams who are subjected to the use of a digital modality (REVIT) to design a commercial kiosk. A coding scheme based on variables of knowledge transformation is employed to generate empirical data from the design protocols. A 4-point Likert scale was also used to validate the coded segments against the designers’ actual intent. Statistical analysis using Chi-Square cross-tabulation has established a significant association between the digital modality (Revit) and the variables. The results indicate that the digital modality is statistically different concerning the distributed frequencies and duration of stages 1, 2 and 4 of knowledge transformation in BIM design. It was found that the BIM modality showed properties that may likely impede the high frequency and duration of personal experience, technical know-how, skills, views, vision, understanding, character, perception, morals and ideas among stakeholders. In conclusion, the study recommends the improvement of the BIM design to support socialisation, externalisation, internalisation, experiential and conceptual knowledge assets, originating ‘ba’ and dialoguing ‘ba’.